2016
DOI: 10.2298/yjor150228019n
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Macedonian banking sector

Abstract: The subject of this paper is to measure the efficiency of the Macedonian banking sector by applying two approaches: firstly, comparative analysis on the efficiency indicators of the banking sector in the Republic of Macedonia and the countries of Central and Southeastern Europe (CSEE) and secondly, Data Envelopment Analysis (DEA). The aim is to provide directions and guidelines for further strengthening of the Macedonian banking sector. According to the comparative analysis of the efficiency indicators (net in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…In such terms, certain insufficiencies in the accounting indicators approach to efficiency measurement can be eliminated and conclusions about the efficiency can be improved using the DEA approach. Application of the DEA methodology in efficiency measurement has a wide scope and has been used extensively to assess school efficiency [23,28]; hospital efficiency [13]; bank efficiency [1,4,12,14,15,17,19,20,21,22,24,25,26,27]; insurance company efficiency [9,10,15,18], etc. In reviewing the literature, the conclusion is that most studies deal with similar approaches in measuring the relative efficiency of banks over a period of time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In such terms, certain insufficiencies in the accounting indicators approach to efficiency measurement can be eliminated and conclusions about the efficiency can be improved using the DEA approach. Application of the DEA methodology in efficiency measurement has a wide scope and has been used extensively to assess school efficiency [23,28]; hospital efficiency [13]; bank efficiency [1,4,12,14,15,17,19,20,21,22,24,25,26,27]; insurance company efficiency [9,10,15,18], etc. In reviewing the literature, the conclusion is that most studies deal with similar approaches in measuring the relative efficiency of banks over a period of time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…No significant difference between performance of banks in different entities of Bosnia and Herzegovina and those smaller and larger banks were noticed. A comparative analysis of banking sector efficiency indicators in the Republic of Macedonia in the period from 2007 to 2012 and the 16 CSEE countries for the period [2003][2004][2005][2006][2007][2008][2009][2010][2011][2012] shows that the values of observed indicators shifted around the average value for the entire analyzed sample, suggesting that countries with banking sectors that exhibit lower operating costs had a higher level of financial deepening and greater degree of financial intermediation [20]. At the same time, results of DEA approach suggest that the group of large banks with the highest efficiency was in the Macedonian banking sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the financial sector in both countries is improving, they are still relatively underdeveloped and inefficient (c.f. Giustinani & Ross, 2008, and Naumovska & Cvetkoska, for Macedonia and Vorobey, and Gicquel et al. for Kyrgysztan).…”
Section: Introductionmentioning
confidence: 98%
“…In the Republic of North Macedonia, the authors have found the following papers regarding the application of DEA in banks: Micajkova and Poposka [17], Naumovska and Cvetkoska [18], Naumovska and Cvetkoska [19], and FotovaČiković and Cvetkoska [12] ( Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The average efficiency of the Macedonian banking sector has been the highest in 2008 (90.35%) and the lowest in 2012 (79.83%). Naumovska and Cvetkoska [19] 2007-2013 Inputs -deposits and operating costs; Outputs -loans and net interest revenue…”
Section: Ccr (Outputoriented)mentioning
confidence: 99%